2013
DOI: 10.1111/his.12081
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pure mucocele‐like lesions diagnosed on breast core biopsy

Abstract: Our results provide evidence that pure MLL without atypia diagnosed on NCB is usually associated with a benign outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 27 publications
(56 reference statements)
1
18
1
Order By: Relevance
“…In later years, several other studies reported that ADH, DCIS, and IC are observed with MLTs [10][11][12]. It has been reported that 13-23.1 % of mucocele-like lesions (MLLs) that were diagnosed by needle biopsy were finally diagnosed as malignant (DCIS or invasive ductal carcinoma) by excision biopsy [13][14][15][16]. Sutton et al performed excisional biopsy in 38 out of 50 patients with MLL and diagnosed 5 patients with DCIS, 4 patients with ADH, and 29 patients with benign lesions [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In later years, several other studies reported that ADH, DCIS, and IC are observed with MLTs [10][11][12]. It has been reported that 13-23.1 % of mucocele-like lesions (MLLs) that were diagnosed by needle biopsy were finally diagnosed as malignant (DCIS or invasive ductal carcinoma) by excision biopsy [13][14][15][16]. Sutton et al performed excisional biopsy in 38 out of 50 patients with MLL and diagnosed 5 patients with DCIS, 4 patients with ADH, and 29 patients with benign lesions [15].…”
Section: Discussionmentioning
confidence: 99%
“…They consequently concluded that: ''it is reasonable that women with the core biopsy diagnosis of MLL without atypia and no associated mass be offered close clinical follow-up as an alternative to surgery''. In addition, Rakha et al also concluded that: ''if no atypia is present, excision with a vacuum-assisted device after multidisciplinary discussion may be a reasonable alternative to diagnostic surgical excision'' [16]. Specifically, they indicated that 2 out of 54 patients (4 %) with MLL without atypia based on a core biopsy had DCIS in the subsequent excision specimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study of MLLs, Chinyama and Davis ( 1996 ) reported association of MLL with ADH, DCIS and mucinous carcinoma. However, in a review of 54 core biopsies of MLL without atypia which were managed as B3 lesions, Rakha et al ( 2013 ) identifi ed only two low-grade cancer (4 %); and review of the literature in the same publication identifi es four cancers out of 106 MLLs without atypia. Carder and colleagues recommended excisional biopsy on diagnosis of the MLL on core biopsy.…”
Section: Mucocoele-like Lesions (Mlls)mentioning
confidence: 99%
“…However, in a review of 54 core biopsies of MLLs without atypia which were managed as B3 lesions, Rakha et al ( 2013 ) identifi ed only two low-grade cancers (4 %); and review of the literature in the same publication identifi ed four cancers out of 106 MLLs without atypia. However, in a review of 54 core biopsies of MLLs without atypia which were managed as B3 lesions, Rakha et al ( 2013 ) identifi ed only two low-grade cancers (4 %); and review of the literature in the same publication identifi ed four cancers out of 106 MLLs without atypia.…”
Section: Management Of Mllsmentioning
confidence: 99%